Revitalization BMT and Cooperatives Function in Developing Syari'ah Economy - Ach Baihaki (University of Islam Malang, 2017)
The growth of Islamic economics have been more improvement, as in infrastructure, assets and number of employee year of the year. But by that improvement, there are some problems to be payed attention, like development of quality of human resources in Islamic economics system with holistic approach. So that, to strengthen the character of Islamic economics system need to restore it’s concept to the nature of Islamic thought consider with the Islamic economics history and also accommodate local wisdom. To support the improvement of Islamic economics proper with ideology objectives of islam, cooperation and BMT should be have priority to increase their functions and responsibilities in economics development. Operational of cooperation and BMT will make variability of Islamic contracts more variative. Then Islamic contract by partnership approach based profit and losses sharing will have more proportions and cost of control also will be more efficient and worries about information asymmetry will be declined. It caused, awareness of partnership and togetherness to increase cooperation member welfare will be easily achived.Keywords: business entity, Islamic Financial Institutions, Cooperation, BMTJudul Asli : Revitalisasi Fungsi BMT dan Koperasi dalam Pengembangan Ekonomi Syari’ah